(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Since 2011, the Nutrition Installation of Panti Rapih Hospital has served diet catering for outpatients. The difference between diet catering services and catering in general is that the food served is very individualized and in accordance with the principles of health nutrition science which provides nutritional interventions according to the results of the assessment of health conditions and data patient base. The success of the implementation of diet catering in hospitals can be seen from customer satisfaction. Customer satisfaction assessment is an effective, inexpensive and easy approach in an effort to maintain service quality. This study aims to determine the factors that influence the level of satisfaction of Diet Catering customers at Panti Rapih Hospital, Yogyakarta. The design of this study was cross-sectional. Respondents are diet catering customers at Panti Rapih Hospital (n=30). The data were analyzed using the Chi-square test. The results showed that the gender of the respondents consisted of 60 percent female and 40 percent male. The age of respondents aged 40 years was 83.3 percent and those aged less than 40 years were 16.7 percent (5 people). Respondents who are satisfied with diet catering services are 70 percent and those who are not satisfied are 30 percent. Conclusion: The results of the Chi-Squared test showed that there was a significant effect between food taste, food appearance, menu variations and equipment cleanliness with the level of catering customer satisfaction (p